PENGARUH KUALITAS PELAYANAN DAN KEPUASAN NASABAH TERHADAP KEPERCAYAAN NASABAH DAN LOYALITAS NASABAH PENABUNG AKTIF PT BANK BUKOPIN CABANG BANJARMASIN - Akhmad Darma Putera; Juhriyansyah Dalle; Muhammad Riduansyah Syafari (JURNAL BISNIS DAN PEMBANGUNAN, 2021)
The aim of this research is to analysis the effects of quality services and customer satisfaction on customer loyalty with mediating customer trust of the activesavers. This research is an explanatory-causality which tests and analysis 5 direct effects and 2 mediation effect. Target population of this research is the activesavers/customer PT Bank Bukopin Banjarmasin Branch. The quantitative data is processed using Structural Equation Modeling (SEM), aided by SmartPLS Software.The research findings demonstrate that (1) service quality have positive signifikan effect on customer trust (H1) and on customer loyalty (H2); (2) customer satisfaction positif insignificance effect on customer trust, but positive significance effect on customer loyalty; (3) customer trust have positive significance effect on customer loyalty (H5); (4) customer trust have positive significance partially-mediation the effect of quality service on customer loyalty (H6); and (5) customer trust no mediation the effect of customer satisfaction on customer loyalty. The power relevant predictive this loyalty model at minimum moderate/medium.Keywords: Quality Service, Customer Satisfaction, Customer Trust, and Customer Loyalty.